Job loss and the mental health of spouses and adolescent children - Melisa Bubonya; Deborah A. Cobb-Clark; Mark Wooden (IZA Journal of Labor Economics, 2017)
Panel data from the Household, Income and Labour Dynamics in Australia Survey are used to examine the impact of involuntary job loss on the mental health of spouses and adolescent children. Estimates from fixed effects models show that the mental health of women (but not men) declines following a spouse's job loss, but only if that job loss results in a sustained period of non-employment or if the couple experienced prior financial hardship or relationship strain. A negative effect of parental job loss on the mental health of adolescent children is also found but is restricted to girls.
Keywords: I31; J10; J65; 330; Unemployment; Involuntary job loss; Mental health; Families; Spouses; Adolescents; HILDA Survey